Teaching Translation to Different Age Groups - Bektemir, Gafforov (European Journal of Life Safety and Stability (2660-9630), 2022)
The purpose of this article is to take into account the characteristics that should be taken into account by the teacher in the process of teaching a foreign language to students of different ages. The article shows the difficulties faced by students in the process of mastering translation skills, some teaching methods of teaching students of different age groups, as well as the value of motivation and translation for students in the process of learning foreign language methods.